2021
DOI: 10.3390/vetsci9010012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risk Factors, Antimicrobial Resistance and Molecular Characterization of Salmonella in Northeast Tunisia Broiler Flocks

Abstract: This study was conducted in northeastern Tunisia to estimate both the prevalence and the risk factors of Salmonella in broiler flocks as well as to characterize the isolated multidrug-resistant (MDR) Salmonella strains. In the present study, a total number of 124 farms were sampled; Salmonella isolates were identified by the alternative technique VIDAS Easy Salmonella. The susceptibility of Salmonella isolates was assessed against 21 antimicrobials using the disk diffusion method on Mueller–Hinton agar using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Colistin resistance has been detected in Escherichia coli isolates from both apparently healthy chickens or poultry meat [ 16 , 25 , 31 , 32 , 33 ] and chickens that died due to colibacillosis [ 34 ], as well as in Salmonella spp. isolates in broiler flocks [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colistin resistance has been detected in Escherichia coli isolates from both apparently healthy chickens or poultry meat [ 16 , 25 , 31 , 32 , 33 ] and chickens that died due to colibacillosis [ 34 ], as well as in Salmonella spp. isolates in broiler flocks [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this study is the first investigation conducted in Tunisia in which all the mcr gene types known so far have been examined. In this regard, previous studies have shown a mismatch between phenotypic colistin resistance and the detection of mcr genes in some bacterial isolates [ 16 , 35 ]. The lack of evidence of mcr genes in DNA from colistin resistant isolates could be attributed to classic chromosomal mutations as well as the presence of untested mcr variants.…”
Section: Discussionmentioning
confidence: 99%
“…The skin and meat of carcasses are frequently infected with the pathogen during slaughter and processing (FAO, 2022). several studies have reported Salmonella prevalence in broiler farms as 34.37%, 24%, 19.9%, in Algeria, Morocco, and Tunisia, respectively (Chaiba and Rhazi Filali, 2016;Djeffal et al, 2018;Oueslati et al, 2021). Therefore, it is important to consider farm contamination, which represents a critical stage in the development of Salmonella, both in terms of its impact on public health and the significant economic repercussions it can generate (Chaiba and Rhazi Filali, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The global spread of S. Kentucky, especially in Europe, Africa and Asia, has been illustrated by the isolation of a particular epidemic clone (S. Kentucky ST198-X1) in different reservoirs of livestock, especially in poultry, chicken and turkey farms. For this purpose, poultry are considered the main potential vectors of human infection [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene amplicons were visualized in 1.5% agarose gel stained with ethidium bromide and photographed under UV transilluminate. Positive and negative controls represented by Salmonella strains isolated in a previous study [ 27 , 52 ] and distilled sterile water were added in each PCR run, respectively.…”
Section: Methodsmentioning
confidence: 99%